Obstructive sleep apnoea - West, S; Turnbull, C (Nature Publishing Group, 2018)
Obstructive Sleep Apnoea (OSA) is increasing in prevalence due to rising obesity. Whilst OSA is a disorder primarily of the upper airway during sleep, its pathophysiological impact on other body systems is increasingly recognised. There has been interest in the prevalence of OSA in different ophthalmic conditions and possible causation has been postulated. As OSA is common, it can be expected that people with coexistent OSA will be found in any ophthalmic disease population studied. To determine with confidence the significance of finding patients with OSA in a particular cohort requires a well matched control group, ideally matched for age, obesity, gender and comorbidities. Only if one can say with certainty that the prevalence of OSA is higher in a group with a particular co-existent ophthalmic disease can we begin to speculate about possible mechanisms for the overlap in these conditions. Possible mechanisms for how OSA might affect the eye are discussed in this review. The current literature is reviewed with respect to diabetic retinopathy, glaucoma, floppy eyelid syndrome, non arteritic ischaemic optic neuropathy, keratoconus and AMD. Associations with OSA have been found, but robust prospective studies using multi-channel sleep studies to diagnose OSA are lacking. Gaps remain in the evidence and in our knowledge. It is hoped that this review will highlight the need for ophthalmologists to consider OSA in their patients. It also makes recommendations for future research, especially to consider whether therapies for OSA can also be effective for ophthalmic disorders.